2018
DOI: 10.1186/s13014-018-1045-7
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features of radiation cataract in patients with ocular adnexal mucosa-associated lymphoid tissue lymphoma

Abstract: BackgroundTo examine the clinical features of radiation cataract in patients with ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphoma.MethodsTwenty-one patients with 26 eyes diagnosed with ocular adnexal MALT lymphoma (26 eyes), who were treated in Hokkaido University Hospital, were retrospectively reviewed based on medical records.ResultsOut of the 21 patients, 16 patients (21 eyes) received radiation therapy (RT) with a total dose of 30 Gy. All cases eventually achieved complete remission. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…16 A few limited case series describing incidence and surgical outcomes of phacoemulsification after EBRT for ocular adnexal mucosa-associated lymphoid tissue lymphoma are described in the literature. 8,9,13,14,16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 A few limited case series describing incidence and surgical outcomes of phacoemulsification after EBRT for ocular adnexal mucosa-associated lymphoid tissue lymphoma are described in the literature. 8,9,13,14,16…”
Section: Discussionmentioning
confidence: 99%
“…Although this cohort is at an increased risk for early cataract development requiring surgery, surgical outcomes have been described in only very limited case series of 8 to 11 patients because of the generally low-risk profile of cataract surgery. 8,9,11 Despite this low risk, it is known that certain patients are at a greater risk for complication, including, among many others, those with PC plaques. Grading systems that have been developed to quantify the risk for complication after cataract surgery do not consider the potential risk for surgery in eyes treated with previous radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that more than half of patients receiving RT without a lens shield had cataract within 3-9 years following RT. [ 30,33] Cataract is the most common late morbidity in ocular adnexal MALT lymphoma patients treated with RT. The risk of cataract and the latent period between RT and appearance of cataract are dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, in proportion with the efficacy of RT, adverse events such as dry eye, cataract, and retinopathy can occur following. 3,4 The optimal RT dose for the treatment of OAML that can effectively control the tumor and minimize ocular complications at the same time is not yet well established. Recently, some researchers have suggested ultra-low-dose RT (4 Gy) for management of ocular adnexal B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%